DISTANCE LEARNING FOR MUSIC DISCIPLINES IN HIGHER EDUCATION: CHALLENGES AND PROSPECTS - Vyshynskyi, Vitalii; Yahodzynska, Iryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
As a worldwide trend of the modern education distance learning gives the possibility to study many disciplines, nevertheless of the fact, is there a practical component in them, for example music disciplines. Among the Ukrainian universities, at the moment only at the Borys Grinchenko Kyiv University has been developing the system of distance learning using the Moodle platform, including the study of special music disciplines. Distance learning for music disciplines associated with a number of specific difficulties, which increases the requirements for the content of the training online course. Even the best and technologically perfect online course does not guarantee that the student will pass it to the end, if there is no threat to disrupt the implementation of the academic plan. Academic results of passing the online training course about modern classical music, that is already tested at Grinchenko University, gives the opportunity to distinguish the basic qualities of effective distance course for music disciplines, that focuses on students; to outline the basic problems related to its implementation into the educational process, as well as their solutions.